1987
DOI: 10.1210/endo-121-4-1343
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Effects of Growth Hormone on Secretion of Insulin-Like Growth Factor I and Progesterone by Cultured Porcine Granulosa Cells*

Abstract: The observation that GH deficiency delays the onset of puberty has raised the question of the effect of GH on gonadal development. In addition, recent studies in the rat have indicated that GH is able to elevate ovarian levels of immunoreactive insulin-like growth factor I (iIGF-I) in vivo and enhance FSH-induced granulosa cell differentiation in vitro. To evaluate further the possibility of direct effects of GH on ovarian function, we have studied the action of GH on the secretion of iIGF-I and progesterone b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
4
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(90 citation statements)
references
References 20 publications
4
80
4
2
Order By: Relevance
“…Growth hormone is reported to modulate the action of FSH on granulosa cells by up-regulating the local synthesis of insulin-like growth factor-I. The IGF-I amplifies the effect of gonadotropin action at the level of both the granulosa and theca cell [4,5]. Results from the published studies were conflicting regarding the effect of GH during controlled ovarian stimulation for IVF [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Growth hormone is reported to modulate the action of FSH on granulosa cells by up-regulating the local synthesis of insulin-like growth factor-I. The IGF-I amplifies the effect of gonadotropin action at the level of both the granulosa and theca cell [4,5]. Results from the published studies were conflicting regarding the effect of GH during controlled ovarian stimulation for IVF [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Also the type 1 IGF receptor of Leydig cells was up regulated by GH (Lin et al 1988). Furthermore, GH injections to immature, hypophysectomized female rat increase the ovarian content of IGF-I (Davoren and Hsueh 1986), and porcine granulosa cell IGF-I production is GH stimulated in vitro (Hsu and Hammond 1987).…”
Section: Gh Stimulation Of Igf-imentioning
confidence: 92%
“…A small stimulation of progesterone by GH alone was first noted by Hsu and Hammond (1987). More recently Mason et al (1990) reported a potent stimulatory effect of hGH (10 ng/ml for 48h) on the production of E 2 by human granulosa cells, which was not dependant on FSH action.…”
Section: Evidence For Direct Gonadal Site Of Action For Ghmentioning
confidence: 92%
See 2 more Smart Citations